Nanocoating Polifenol Sebagai Bahan Pengawet Alami pada Buah-Buahan - Atikah Halimah Putri; Depi Rapika; Shifa Amadea Defiana (Jurnal Kimia Fullerene, 2019)
Utilization of natural ingredients as a means of supporting health has actually been applied by humans for a long time, especially green tea plants (Camellia sinensis). The high polyphenol content in green tea is used to kill harmful bacteria and also bacteria that cause disease in the oral cavity. This study aims to determine how to optimize the extraction of polyphenols from green tea to produce a large polyphenol extract so that it can be used as an ingredient for edible coating formulations with carrageenan and chitosan as well as to determine the preservation ability of the polyphenol edible coating formulations with carrageenan and chitosan to be used for preservation fruits. The stages of this research include: extraction, characterization, polyphenol content analysis, microbial inhibition test and edible coating formulation. The results of the analysis of the total polyphenol content obtained an average of two tests of 22.05% and in the microbial inhibition test, the optimum concentration of polyphenol extract as an antimicrobial was 0.5%. The most effective edible coating formulations with carrageenan and chitosan for tomatoes are polyphenols 0.1%; 0.25%; 0.5%, chitosan-polyphenols 0.5%, and carrageenan-polyphenols 0.25% and caragenan-polyphenols 0.5%. While the most effective coating formulation for grapes is 0.5% polyphenols.